Multiferroic and Optical Properties of La0.05Li0.85NbO3 and LiNbO3 Nanocrystals - Carlos A. Díaz-Moreno; Jorge A. López; Yu Ding; A. Hurtado Macias; Chunqiang Li; Ryan B. Wicker (Journal of Nanotechnology)
The chemistry and physics of surfaces is an increasingly important subject. The study of surfaces is the key of many important nanotechnological applications due to the understanding of phase transitions, electronic structure, and chemical bonding. In later years, exotic phenomena that jointly involve the magnetic and electrical conductivity properties have been discovered in oxides that contain magnetic ions. Moreover, the uses of magnetic oxides in electronic technology have become so important due to the miniaturization of devices and magnetic materials with dielectric properties or vice versa being required for inductors, information storage, thin films for high-density computer memories, microwave antireflection coatings, and permanent magnets for automobile ignitions among others. On the contrary, nanotechnology developments over 10 years or so have provided intensive studies in trying to combine properties such as ferroelectric, ferromagnetic, and optics in one single-phase nanoparticles or in composite thin films; this last effort has been recently known as multiferroic. Because of this, the resurgence of nanomaterials with multiferroic and optical properties is presented in this work of one single phase in lanthanum lithium niobate (La0.05Li0.85NbO3) and lithium niobate (LiNbO3) with ferromagnetic, ferroelectric, relaxor ferroelectricity, second harmonic generation, high-temperature ferromagnetic, and magnetoelectric properties.